Questions of Justification of State Policy Regulation of Production and Consumption of Socially Dangerous Goods and Services - N. I. Fedorova; V. M. Khodachek (Управленческое консультирование)
The purpose of the study is to substantiate a reasonable balance between the interests of consumers and different segments of society in the process of production and consumption of socially dangerous goods and services and to develop recommendations for improving state policy in this area. Various points of view on the solution of the problem are analyzed. Possible options of further strategy of regulation of consumption of this group of goods and services on the example of tobacco products are considered. The methods and mechanisms of regulation that ensure both the protection of public health and the rights of consumers are characterized.